상실을 경험한 대학생의 낙관성이 심리적 안녕감에 미치는 영향: 고통 감내력, 애도 회피, 침투적 반추, 의도적 반추의 매개효과 - 김라영(La Yeoung Kim); 장진이(Jin Yi Jang) (Seuteureseu yeon-gu (Online), 2020)
이 연구는 상실을 경험한 대학생을 대상으로 낙관성, 고통 감내력, 애도 회피, 침투적 반추, 의도적 반추그리고 심리적 안녕감 간의 구조적 관계를 검증하고자 하였다. 또한 이러한 변인들 간의 구조적 관계가상실 경험의 경과 기간이 6개월 미만과 6개월 이상인 집단 간에 유의미한 차이가 있는지를 탐색하고자하였다. 이를 위하여 상실 경험으로부터 평균 수준 이상의 영향을 받은 대학생 435명의 자료를 최종 분석대상으로 하였다. 구조모형 검증 결과, 낙관성과 심리적 안녕감의 관계에서 고통 감내력, 애도 회피, 침투적반추, 의도적 반추의 매개효과가 나타났다. 단, 애도 회피가 직접적으로 심리적 안녕감에 미치는 영향력은유의미하지 않아 이 경로를 제거한 수정 모형이 최종적으로 선정되었다. 이러한 결과를 바탕으로 연구의 의의와 제한점 그리고 추후 연구에 대한 함의를 논의하였다. Background: This study sought to analyze the structural relationships between optimism, distress tolerance, grief avoidance, intrusive rumination, deliberate rumination, and psychological well-being among undergraduates who have experienced a loss. Methods: Subjects comprised 435 university students (258 females and 177 males), with their duration of grief experience and the elapsed period from when the loss occurred having been taken into consideration. Results: Distress tolerance, grief avoidance, intrusive rumination, and deliberate rumination mediated the relationship between optimism and psychological well-being sequentially. Additionally, there were significant differences between the “less than 6 months” and “more than 6 months” groups in the structural relationships between optimism, distress tolerance, grief avoidance, intrusive rumination, deliberate rumination, and psychological well-being. Conclusions: The direct path of grief avoidance to psychological well-being was not significant, but it was found to have a significant effect through the sequential mediations of intrusive rumination and deliberate rumination. This result suggests the need for active intervention to allow people to face and cope with life after a loss, without avoiding the loss experience. KCI Citation Count: 2